Pelatihan Broadcasting Siaran Langsung bagi Siswa Jurusan Multimedia SMK Al-Hikmah 2 Garut - Rohman, Abdul; Kurniawan, Achmad Wildan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: To develope human resources in the multimedia department at SMK Al-Hikmah 2 Garut with a focus on multimedia broadcasting and live streaming. Methodology: Literacy, discussion, collaboration, action, and publication methods. Results: An increase in understanding of live broadcasting material by 92% and video camera usage improved to 88.9%. Eleventh-grade students at SMK Al-Hikmah 2 Garut now grasp the basic concepts of multimedia broadcasting and live streaming. Conclusions: The implementation of this community service activity was successfully carried out, as evidenced by the increased understanding of students regarding broadcasting and live streaming technology. Through this training, students of SMK Al-Hikmah 2 Garut gained a better understanding of using video cameras and Vmix software, despite their initially low level of knowledge. The training showed positive results in enhancing students' skills in the multimedia field. The final evaluation indicated a significant improvement in participants' understanding, although some challenges were encountered regarding facilities and the number of participants. Limitations: One possible limitation is the lack of adequate broadcasting equipment and technology. Students may not be able to get the most out of the experience if the equipment used is not up to industry standards. Contribution: This research is valuable in the field of multimedia education, particularly in vocational schools, for enhancing students' skills in multimedia broadcasting and live streaming.